Composition Characteristics and Potential Regions of PM2.5 during Winter Haze Pollution in Typical Industrial Areas, NW-China - Liyao Guo; Chao Gu; Kaiyuan Dong; Shengju Ou; Xueyan Zhao; Xinhua Wang; Zhensen Zheng; Wen Yang (Aerosol and Air Quality Research)
Abstract To investigative the causes and potential sources of fine particulate matter (PM2.5) pollution during winter haze pollution in typical industrial areas in northwest China, PM2.5 samples were collected during a winter extreme pollution event (from January 15 to January 29, 2016). The daily average PM2.5 concentrations were ~210 µg m–3 and peak daily concentrations were ~496 µg m–3 in the Kuitun-Dushanzi-Wusu (K-D-W region) of Xinjiang Uygur Autonomous Region, China. Eighty-eight samples (including 44 quartz and 44 Teflon samples for PM2.5) were assessed for watersoluble ions (WSIIs), organic/elemental carbon (OC/EC) and inorganic elements. The results showed that the percentage of carbonaceous compounds decreased with more severe pollution levels, and the OC and SOC decreased more rapidly than EC. The sum of 39 inorganic element concentrations (8.28% ± 3.59%) was lower than that of water-soluble ions (63.26% ± 8.78%) and carbonaceous compounds (10.95% ± 3.22%). SO4 2− is the component with the highest percentage, and the percentage of SO4 2− increases continuously in severe pollution, indicating that secondary transformation of SO4 2− was more significant during polluted periods. The increased pollution, combined with high relative humidity (RH) increased the liquid water content (LWC), which in turn promoted heterogeneous reactions. The Positive Matrix Factorization (PMF) analysis shows that secondary particulate matter (47%), coal combustion (19%), fugitive dust (14%), industrial sources (10%) and vehicular emissions (10%) are identified as the major emission sources during winter in the K-D-W region. Potential areas in the K-D-W region are distributed in the southeast direction of the 8th Division.